Pleural Rosai-Dorfman disease complicated with renal clear cell carcinoma: a case report and literature review - Tang, Sudan; Yang, Xinju; Wang, Shunan; Xiao, Qin (Frontiers in Oncology, 2025)
BackgroundRosai-Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy, is a rare non-malignant disorder characterized by excessive proliferation of histiocytes, the cause of which remains unknown. Although the lymph nodes are the most commonly affected site, some patients may present with extranodal involvement, particularly in the skin, nasal cavity, eyes, and bones. In this report, we aim to present a unique case of RDD with pleural involvement in a 61-year-old patient. To our knowledge, only a few cases of RDD primarily manifesting as pleural disease have been reported thus far.Case summaryA 61-year-old male with left brachial plexus neuropathy was found to have a space-occupying lesion in the left posterior pleura. Initial chest CT showed a 5.7cm × 1.3cm soft tissue density shadow, which grew to 6.8cm × 1.7cm two years later. Given a history of clear cell renal cell carcinoma, pleural metastasis was suspected. The patient declined a needle biopsy but underwent surgical excision. Postoperative pathology and immunohistochemistry confirmed Rosai-Dorfman disease (RDD). After surgery, the patient received anti-infection, phlegm reduction, rehydration, and analgesia treatments and recovered well.ConclusionRDD originating in pleura is rare, its clinical and imaging manifestations lack specificity, and it is easy to be misdiagnosed. It is crucial to consider the possibility of RDD when encountering nodular pleural masses or lamellar soft tissue lesions. Differential diagnosis should include pleural mesothelioma, pleural metastases, solitary fibrous neoplasms, and schwannomas of the pleura. Ultimately, a definitive diagnosis can be achieved through pathology and immunohistochemistry analysis.